Integrative review on biology, water quality and the order Odonata (Research, Society and Development, 2021)
Sciences such as biology generate information about ecosystems, such as aquatic ecosystems, and promote integration with ethnic knowledge associated with botany. The objective of this work was to carry out an integrative review about the interrelationship of biology with various environmental areas, under two aspects, conservation, and balance, to investigate the relationship between biology and research on water quality and the use of the order Odonata as bioindicator of the environmental quality of water bodies. The research method was deductively associated with a quantitative and qualitative approach of a basic nature. The data obtained and analyzed indicated that the biological terms are present in most of the selected literature (n = 46.2%); regarding water quality, there was a small reduction (n = 30.8%); the use of the order Odonata as bioindicators of water quality is still scarce (n = 22.9%). As for the use of descriptors in the analyzed research, the following citations were identified: "Biological terms and water quality" (n = 65.8%); "Odonata and water quality" (n = 21.1%); "Biological terms and Odonata" (n = 13.2%). The order Odonata, as a bioindicator, is evolving (Ʃ = 33.3%) and with high frequency (fr > 50%) when compared to the application of Biological Terms and Water Quality. So, the application of biology is already effective in environmental areas such as water quality analysis. However, the use of Odonata as bioindicators of water quality is not used very often yet. Thus, it is recommended that there is a greater appreciation by researchers of this relationship, which can contribute to the qualification and monitoring of this natural resource more comprehensively and effectively.